Phosphorylation of Microtubule- Associated Protein 4 Promotes Hypoxic Endothelial Cell Migration and Proliferation - Zhang, Junhui; Li, Lingfei; Zhang, Qiong; Yang, Xu; Zhang, Can; Zhang, Xingyue; Zhang, Dongxia; Lv, Yanling; Song, Huapei; Chen, Bing; Liu, Yao; Hu, Jiongyu; et al. (Frontiers in Pharmacology, 2019)
Endothelial cells play a critical role in vessels in the process of angiogenesis during skin wound healing. The migration and proliferation of endothelial cells could be initiated by hypoxic microenvironment in a wound, while the underlying mechanisms remain largely unknown. Here we identify a novel role for microtubule-associated protein 4 (MAP4) in angiogenesis. We firstly demonstrate that MAP4 phosphorylation is induced in hypoxic endothelial cells; the increase of MAP4 phosphorylation enhances the migration and proliferation of endothelial cells. We also find that hypoxia (2% O2) activates p38/MAPK signaling and identify p38/MAPK as an upstream regulator of MAP4 phosphorylation in endothelial cells. Moreover, we show that the promigration and proproliferation effects of MAP4 phosphorylation are attributed to its role for microtubule dynamics. These results indicate that MAP4 phosphorylation induced by p38/MAPK signaling enhances angiogenesis by promoting proliferation and migration of endothelial cells via regulation of the microtubule dynamics under hypoxia, which provide new insights into the potential mechanisms underlying the initiation of migration and proliferation in endothelial cells.